Karis-Gerhart collection : from protest to challenge, 1964-1990 - Karis, Thomas, 1919-; Gerhart, Gail M. ([Cooperative Africana Microfilming Project] : [Available from Center for Research Libraries], 1999)
Consists of primary source documents compiled by Thomas Karis and Gail M. Gerhart in the process of writing vols. 5-7 of: From protest to challenge : a documentary history of African Politics in South Africa, 1882-1990.